A simple procedure to produce bio-mimic brick-and-mortar microstructure in commercially pure Ti. Issue 1 (1st July 2022) - Liu, Chengze; Xu, Jianping; Li, Huan; Zhang, Yusheng
Abstract: The extremely high fracture toughness of nacre is known to arise from its brick-and-mortar microstructure and has inspired the development of metals, metallic glasses and composites with similar bio-mimic microstructures. Although various approaches have been proposed to produce materials with a brick-and-mortar microstructure, including powder metallurgy, electro deposition, spray deposition, etc., the production of large-scale samples remains to be a challenge. In this research, we present a simple way to produce large samples of commercially pure Ti with a brick-and-mortar microstructure, which includes a pre-heat-treatment followed by deformation in the single-phase temperature region and subsequent annealing. EBSD characterization shows a layered microstructure in the produced samples resembling a brick-and-mortar structure.